Effects of Chicken Interferon Gamma on Newcastle Disease Virus Vaccine Immunogenicity - Cardenas-Garcia, Stivalis (PLoS One, 2016)
More effective vaccines are needed to control avian diseases. The use of chicken interferon gamma (chIFNγ) during vaccination is a potentially important but controversial approach that may improve the immune response to antigens. In the present study, three different systems to co-deliver chIFNγ with Newcastle disease virus (NDV) antigens were evaluated for their ability to enhance the avian immune response and their protective capacity upon challenge with virulent NDV. These systems consisted of: 1) a DNA vaccine expressing the Newcastle disease virus fusion (F) protein co-administered with a vector expressing the chIFNγ gene for in ovo and booster vaccination, 2) a recombinant Newcastle disease virus expressing the chIFNγ gene (rZJ1*L/IFNγ) used as a live vaccine delivered in ovo and into juvenile chickens, and 3) the same rZJ1*L/IFNγ virus used as an inactivated vaccine for juvenile chickens. Co-administration of chIFNγ with a DNA vaccine expressing the F protein resulted in higher levels of morbidity and mortality, and higher amounts of virulent virus shed after challenge when compared to the group that did not receive chIFNγ. The live vaccine system co-delivering chIFNγ did not enhanced post-vaccination antibody response, nor improved survival after hatch, when administered in ovo, and did not affect survival after challenge when administered to juvenile chickens. The low dose of the inactivated vaccine co-delivering active chIFNγ induced lower antibody titers than the groups that did not receive the cytokine. The high dose of this vaccine did not increase the antibody titers or antigen-specific memory response, and did not reduce the amount of challenge virus shed or mortality after challenge. In summary, regardless of the delivery system, chIFNγ, when administered simultaneously with the vaccine antigen, did not enhance Newcastle disease virus vaccine immunogenicity.